Developing Atom Probe Tomography of Phyllosilicates in Preparation for Extra‐Terrestrial Sample Return. Issue 3 (7th May 2021) - Daly, Luke; Lee, Martin R.; Darling, James R.; McCarrol, Ingrid; Yang, Limei; Cairney, Julie; Forman, Lucy V.; Bland, Phillip A.; Benedix, Gretchen K.; Fougerouse, Denis; Rickard, William D. A.; Saxey, David W.; et al.
Abstract : Hydrous phyllosilicate minerals, including the serpentine subgroup, are likely to be major constituents of material that will be bought back to Earth by missions to Mars and to primitive asteroids Ryugu and Bennu. Small quantities (< 60 g) of micrometre‐sized, internally heterogeneous material will be available for study, requiring minimally destructive techniques. Many conventional methods are unsuitable for phyllosilicates as they are typically finely crystalline and electron beam‐sensitive resulting in amorphisation and dehydration. New tools will be required for nanoscale characterisation of these precious extra‐terrestrial samples. Here we test the effectiveness of atom probe tomography (APT) for this purpose. Using lizardite from the Ronda peridotite, Spain, as a terrestrial analogue, we outline an effective analytical protocol to extract nanoscale chemical and structural measurements of phyllosilicates. The potential of APT is demonstrated by the unexpected finding that the Ronda lizardite contains SiO‐rich nanophases, consistent with opaline silica that formed as a by‐product of the serpentinisation of olivine. Our new APT approach unlocks previously unobservable nanominerals and nanostructures within phyllosilicates owing to resolution limitations of more established imaging techniques. APT will provide unique insights into the processes and products of water/rock interaction on Earth, Mars and primitive asteroids. Abstract : Key Points Here we show a novel approach to measure phyllosilicates by atom probe tomography for the first time revealing an SiO-rich nanophase within serpentine. This capability is particularly important with the upcoming delivery of similar minerals from sample return missions Hayabusa 2 and OSIRIS-REx to water rich asteroids and the Mars Sample Return campaign.